Analysis of cadmium heavy metal content in rice snail (Pila ampullacea) from Rawa Taliwang Lake - Indra Wulan; Khairuddin Khairuddin; Muhammad Yamin (Jurnal Pijar Mipa, 2023)
Snails are one of the aquatic organisms that can be used as biological indicators of heavy metals in water. This study aims to determine the amount of cadmium heavy metal content in rice snails (Pila ampullacea) from Rawa Taliwang Lake, which can be used to enrich lecture material on environmental knowledge and to determine the feasibility of consumption of rice snails (Pila ampullacea) in accordance with the threshold of heavy metal contamination in food. The research was conducted over ten months, from August 2022-June 2023, at Rawa Taliwang Lake. Data were collected using the purposive sampling method at two research stations, namely the East and West sides. The samples in this study were four rice snails caught using a net. The samples were then deconstructed and analyzed using Atomic Absorption Spectrophotometry (AAS). The rice snail body parts studied were the flesh cleaned and separated from the shell and internal organs. The analysis showed that the average cadmium (Cd) heavy metal content in the flesh of rice snails (Pila ampullacea) from Rawa Taliwang Lake was 0.19 mg/kg, which means that it is suitable for consumption because it is below the maximum threshold of cadmium (Cd) contamination allowed in gastropods which are 0.30 mg/kg according to the Food and Drug Administration Regulation No. 9 of 2022.